KORELASI KEPATUHAN IBU HAMIL MENGONSUMSI TABLET FE BERBASIS APLIKASI DENGAN KADAR HB BERDASARKAN KARAKTERISTIK DEMOGRAFIS - Susanti, Ari Indra; Novianti, Shofi Nabila; Mandiri, Ariyati; Rinawan, Fedri Ruluwedrata; Wardani, Yusrima Syamsina (Media Penelitian dan Pengembangan Kesehatan, 2025)
Non-compliance of pregnant women in consuming iron (Fe) tablets can lead to low hemoglobin (Hb) levels, increasing the risk of anemia. Some mothers attempt to use mobile phone alarms as reminders; however, this method is less effective as it does not record the number of tablets consumed. Therefore, a reminder in the form of an alarm through the iPosyandu Keluarga application is needed to help mothers consistently take Fe tablets. This study aims to analyze the correlation between pregnant women's compliance in consuming Fe tablets using the iPosyandu Keluarga application and Hb levels based on demographic characteristics. This research employed an analytical cross-sectional design conducted in February 2024 in the working area of the Margajaya Health Center, involving 58 pregnant women selected through purposive sampling. Characteristic data were obtained from the back-end system of the iPosyandu Keluarga application, and Hb levels were measured after 30 days of Fe tablet consumption. Data analysis was performed using the Spearman test. The results of this study showed a strong correlation between the compliance of pregnant women based on the iPosyandu keluarga  application and Hb levels (p-value <0.05; r value = 0.60-0.799). However, there was no correlation between the compliance of pregnant women in consuming Fe tablets and characteristics (p-value> 0.05; r value = 0.00-0.199). The conclusion of this study shows that the use of the iPosyandu keluarga application is related to the compliance of pregnant women in consuming Fe tablets with Hb levels, without any relation to demographic characteristics.